Introducing competition in the European rail sector insights for a holistic regulatory assessment - Yves Crozet (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
This paper assesses the impact of European rail transport regulation in the past 25 years. It highlights competition as a necessary condition to overcome the inertia of legacy railway operators, but argues that competition is not sufficient to increase efficiency when they feel protected by the state.
Keywords: 330; Eisenbahnunternehmen; Regulierung; Wettbewerbsvorteil; EU-Verkehrspolitik; EU-Staaten